Peningkatan Hasil Belajar Siswa dengan Model STAD Berbantuan Media Tangga Pintar pada Siswa Kelas II SD 2 Singocandi - Khoirina, Faza Nuril Ulya; Masfuah, Siti; Nilamsari, Tianida (Lembaga Yasin AlSys, 2025)
This study was conducted to address the problem of low student achievement in mathematics, which is attributed to the lack of appropriate instructional models and media. As a solution, the Student Teams Achievement Division (STAD) cooperative learning model was employed, combined with the use of a